Disclosure of social responsibility in a furniture factory in the Cai Valley - Rio Grande do Sul - Naime, Roberto; Selbach, Eduardo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper performs systematic surveys of the actions performed by the manufacturer of the furniture worth Cai to encourage and promote the participation of employees and the community in which it is embedded in social responsibility. These initiatives stem from demands generated by interested parties (stakeholders) and that the organization seeks to satisfy and highlight the most efficient way to fulfill their social roles within the community expectations and perceptions, seeking to qualify his organizational work environment in search of general sustainability and best conditions of quality of life for all.